Seminar Pengembangan Omset UMKM Dengan Sertifikasi Halal - Rafi Ilham Ramadhan; Mohammad Rasikhul Islam; Khoirotun Nisa’; Siti Nur Halizah; Eli Retnowati; Rommy Hardyansah; Rio Saputra (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
Currently, providing halal certification for a product has become a necessity. Consumers are now more careful when choosing halal-certified products before consuming them. In Jumputrejo Village, Sukodono District, Sidoarjo Regency, there are a number of Micro, Small and Medium Enterprises (MSMEs) that have not obtained halal certification. Therefore, the KKN team from Sunan Giri University Surabaya has held a seminar on Increasing MSME Turnover through Halal Certification, with the aim that local MSMEs can obtain halal certification. The process of implementing this seminar consists of three stages, namely (1) planning, which involves mapping the problem; (2) finding solutions to the problem; and (3) coordination with MSME partners. The implementation of the seminar on turnover development through halal certification was carried out using the method of delivering material and question and answer sessions. The results of this activity show that MSME partners who attended the seminar showed enthusiasm in asking questions related to halal products, the benefits of halal-labeled products, and the procedures for receiving halal certification.